The Future Health Workforce: Integrated Solutions and Models of Care - Balasubramanian, Madhan; Short, Stephanie (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This edited collection brings together a diverse set of original research and review articles that contribute towards a unified objective of redesigning the future health workforce. Our fundamental premise is that the future health workforce needs to be more closely aligned to population needs and be able to address emerging challenges of the 21st century. • The collection includes 13 articles (11 original research; 2 review) from nine countries. • Original research articles that contributed to this special issue came from Australia, Brazil, Canada, China, Japan, South Korea, Sweden, the United Kingdom and the United States of America. • The collection features a range of health professionals including medical, dental, nursing, allied health, social work, and health management workforce. This unique piece of scholarship adds to ongoing global efforts on health workforce integration, universal health coverage, and creating sustainable and people-centric health systems